Analysing the Economic Impact of the Indian Music Industry: Trends, Challenges, and Opportunities in the Digital Era - Dr. Sangeeta (Sampreshan, ISSN:2347-2979 UGC CARE Group 1, 2024)
The Indian music industry, deeply rooted in the country's cultural diversity, has entered a transformative phase in the digital era, marked by significant economic implications. This paper aims to analyze the economic impact of this industry, focusing on the evolving trends, challenges, and opportunities that have emerged with the advent of digital technology. Historically dominated by Bollywood music, the industry has witnessed a paradigm shift with the proliferation of digital platforms, streaming services, and social media, which have broadened its reach and altered consumption patterns. While these developments have opened new revenue streams and facilitated the rise of independent artists and labels, they have also disrupted traditional revenue models and intensified competition. The economic influence of the Indian music industry extends to job creation, tourism, and international trade, yet it faces critical challenges like piracy, copyright issues, and uneven technological access across India. This paper provides a comprehensive examination of these dynamics, exploring how the Indian music industry navigates the complex terrain of the digital era and its broader economic significance.